Numerical investigation on damage effect of deep hole pre-cracking roof rock and controlling rockburst - Qi Hao; Anye Cao; Changbin Wang; Zhongyi Tang; Jiangang Liu (International Journal of Coal Science & Technology, 2025)
Abstract Deep hole pre-cracking blasting (DHPB) technology is the preferred means of preventing and controlling rockburst induced by hard-thick rock layers in coal mines. When DHPB is applied to hard-thick rock layers, the insufficient knowledge about the crack extension scale under different rock properties and blasting parameters may result in undesirable pressure relief. Therefore, LS-DYNA was adopted to analyse the crack extension characteristics under the combined effect of rock tensile strength, explosive density, blasthole spacing, and decoupled coefficient. The Holmquist–Johnson–Cook model (HJC), verified by the results of blasting experiment and numerical simulation in literature, was used to characterise coal-bearing rocks. Numerical analysis was conducted to study the blasting crack extension and fractal damage for rock tensile strength, explosive densities, blasthole spacing, and decoupled coefficients. The results show that the tensile strength of rock is the key factor for blasting design. The fractal damage caused by blasting increases when the tensile strength of rock decreases. For rocks with lower tensile strength, more blasting energy is consumed by the increasing damage area in the crushed zone. Higher explosive density can promote the development of blasting cracks and increase fractal damage, but the increasing range of the crushed zone also wastes a large amount of energy. As the blasthole spacing increases, the fractal damage decreases, and the crack extension scale in the fractured zone first increases and then decreases, and eventually remains almost unchanged. An optimum interval exists for the decoupled coefficient, and the full utilization of explosive energy within the interval leads to penetrating blast cracks and smaller crushed zones. Based on the simulation results, the optimal blasting parameters for coarse sandstone were validated in the field practice. Monitoring data show that the optimized blasting significantly reduces the risk of rockburst.